Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 5 - Section 5.6 - Factoring Trinomials - Exercise Set - Page 304: 107



Work Step by Step

RECALL: $a^2-2ab+b^2=(a-b)^2$ The given trinomial can be written as: $\\=(2x^n)^2-2(2x^n)(3)+3^2$ This is in the same form as the formula above where $a=2x^n$ and $b=3$. Use the formula above to have: $\\=(2x^n-3)^2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.